(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to identify the reality of the responsibilities of the Board of Directors and its role in enhancing creativity and organizational development in commercial banks operating in the western region of Libya. The study community represented all administrative leaderships from the first and second ranks (the Chairman and members of the Board of Directors - directors of the control and supervisory departments and their deputies - general managers and their deputies - department managers and their assistants) in the commercial banks under study, numbering (315) individuals. Due to the small size of the study community, the comprehensive survey method was used to collect data from the individuals targeted by the study. The questionnaire was also relied upon as the main tool for collecting data. The number of these distributed questionnaires was (318), with (53) questionnaires for each bank. (258) valid questionnaires were retrieved for analysis, and (60) questionnaires were lost or unfit for analysis. The return rates for each bank ranged between 73.6% and 88.7%, and the return rate for the total of the community was 81.1%, which is a return rate of the study concluded with several important findings, the most important of which are: -1 It was evident that there is a clear decline in the level of boards of directors’ responsibility in the commercial banks under study. The average response of the study’s members to this variable was (2.99779), which is lower than the level adopted in the study. 2- It was evident that there is a decline in the innovation and development process in the commercial banks under study. The average response of the study’s members to this variable was (2.87209), indicating that they confirm the existence of a clear deficiency in the innovation and development process in these banks. 3- There is a statistically significant effect at the significance level (0.05) of the responsibilities of the Board of Directors in promoting the innovation and development process in the commercial banks under study. This means that the independent variable (responsibilities of the Board of Directors) explains 49.1% of the variance in the dependent variable (innovation and development) for these banks. This validates the hypothesis on which the study was based. The study also recommended the following: 1- The study recommends developing a clear strategy for innovation and creativity that aligns with long-term goals, with an independent budget allocated for research and development (R&D). 2- Emphasize and focus on instilling a culture of innovation and creativity by encouraging employees to propose new ideas in exchange for rewards for successful innovations, while allowing ideas to be tested without fear of punishment. 3- Involve customers in the development process by adopting an open innovation approach, surveying their opinions and developing solutions based on them.